2023
DOI: 10.1186/s13063-022-06998-z
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomized, placebo-controlled trial to evaluate the efficacy of a spatial repellent (Mosquito Shield™) against Aedes-borne virus infection among children ≥ 4–16 years of age in the Gampaha District, Sri Lanka: study protocol (the AEGIS program)

Abstract: Background Spatial repellents (SRs) have been widely used for prevention of mosquito bites, but their efficacy in reducing Aedes-borne viruses (ABV) has not been tested rigorously at large scale in Asia. To address this knowledge gap, a trial to evaluate the efficacy of Mosquito Shield™, a transfluthrin SR, was developed in Gampaha District of Sri Lanka across three Medical Officer of Health areas; i.e., Negombo, Wattala, and Kelaniya. Methods This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…In addition to the Wolbachia infected mosquitoes, the use of spatial repellents is been investigated [47,51]. A trial in Peru showed that the use of spatial repellents significantly reduced the Aedes aegypti abundance by 28.6% and the incidence of vector transmitted infection by 34.1% [47].…”
Section: Impact Of Novel Vector Control Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the Wolbachia infected mosquitoes, the use of spatial repellents is been investigated [47,51]. A trial in Peru showed that the use of spatial repellents significantly reduced the Aedes aegypti abundance by 28.6% and the incidence of vector transmitted infection by 34.1% [47].…”
Section: Impact Of Novel Vector Control Methodsmentioning
confidence: 99%
“…A trial in Peru showed that the use of spatial repellents significantly reduced the Aedes aegypti abundance by 28.6% and the incidence of vector transmitted infection by 34.1% [47]. Trials evaluating spatial repellents are currently being carried in other sites, such as in Sri Lanka [51], and if found effective, this would be a cheap, easy to use technique for vector control. While these methods have the potential to reduce the burden of dengue in diseaseendemic countries, their effectiveness in the context of increasing vector densities due to climate change and in the case of adaptation to the effects of Wolbachia is not known and should be further studied.…”
Section: Impact Of Novel Vector Control Methodsmentioning
confidence: 99%
“…Cluster randomized controlled trials (cRCTs) [18], in which households, villages, or broader geographical areas ("clusters") are randomly assigned either to the intervention or to the control, are considered to provide the most robust estimates of entomological and epidemiological efficacy with the least opportunity for the introduction of bias from confounding factors, although technical or ethical considerations in some vector control trials may necessitate the use of alterative designs [12,15,16,18,70,71]. cRCTs have previously been used in numerous vector control field trials [15,16], such as those involving ITNs [72] and other insecticide-based interventions [15,16,[73][74][75] including eave tubes [76], or spatial repellants [77][78][79][80], ivermectin mass drug administration [81,82], the wMel strain of Wolbachia pipientis (Rickettsiales; Anaplasmataceae) [83][84][85], and attractive-toxin sugar bait traps [86][87][88].…”
Section: Trial Designmentioning
confidence: 99%